1989
DOI: 10.1007/bf01248932
|View full text |Cite
|
Sign up to set email alerts
|

Variability among brain regions in the specificity of 6-hydroxydopamine (6-OHDA)-induced lesions

Abstract: 6-Hydroxydopamine (6-OHDA; 200 micrograms, 150 micrograms or 110 micrograms) or vehicle was infused stereotaxically into the lateral ventricles of rats, usually following pretreatment with desmethylimipramine (DMI). Various brain regions were then assayed for dopamine (DA), serotonin (5-HT) and norepinephrine (NE). As expected, 6-OHDA depleted DA in all brain regions examined. Unexpectedly, however, the two highest doses of 6-OHDA significantly decreased 5-HT levels in the hippocampus and increased 5-HT levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 22 publications
1
9
0
1
Order By: Relevance
“…However, in some cases, opposite results were obtained using the same 6-OHDA-lesioned rodent model (Guiard et al 2008b ;Kaya et al 2008). It is important to remember that in animal models of PD, striatal serotonin levels have been reported to be increased (Balcioglu et al 2003 ;Commins et al 1989 ;Karstaedt et al 1994 ;Zhou et al 1991) unchanged (Breese et al 1984 ;Carta et al 2006) or decreased (Aguiar et al 2006(Aguiar et al , 2008. These findings indicate that these changes in the serotonergic system may be highly dependent on the location and extension of dopaminergic degeneration.…”
Section: Discussionmentioning
confidence: 52%
“…However, in some cases, opposite results were obtained using the same 6-OHDA-lesioned rodent model (Guiard et al 2008b ;Kaya et al 2008). It is important to remember that in animal models of PD, striatal serotonin levels have been reported to be increased (Balcioglu et al 2003 ;Commins et al 1989 ;Karstaedt et al 1994 ;Zhou et al 1991) unchanged (Breese et al 1984 ;Carta et al 2006) or decreased (Aguiar et al 2006(Aguiar et al , 2008. These findings indicate that these changes in the serotonergic system may be highly dependent on the location and extension of dopaminergic degeneration.…”
Section: Discussionmentioning
confidence: 52%
“…Finally, we examined levels of serotonin in our tissue. Although serotonin neurons are not directly affected by 6-OHDA, there have been conflicting reports about changes in serotonin levels in the dorsal striatum following dopamine depletion (Breese, Baumeister et al 1984, Commins, Shaughnessy et al 1989, Karstaedt, Kerasidis et al 1994, Frechilla, Cobreros et al 2001, Balcioglu, Zhang et al 2003, Carta, Lindgren et al 2006, Rylander, Parent et al 2010) and this has been hypothesized to play a role in L-dopa induced dyskinesias (Nagatsua and Sawadab 2009, Rylander, Parent et al 2010). Interestingly, serotonin levels remained constant until ~60% of dopamine had been lost, then suddenly increased by 10–20% (ANOVA with Dunnett t, p < 0.05 from saline).…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers have reported hyperinnervation (Zhou et al, 1991; Rozas et al, 1998; Balcioglu et al, 2003; Maeda et al, 2003), while others found no sprouting (Prinz et al, 2013), or even a decrease in striatal serotonergic fibers after dopaminergic damage (Takeuchi et al, 1991; Rylander et al, 2010). Along the same lines, striatal 5-HT levels have been found to be increased (Commins et al, 1989; Zhou et al, 1991; Karstaedt et al, 1994; Balcioglu et al, 2003), unchanged (Breese et al, 1984; Carta et al, 2006), or decreased (Frechilla et al, 2001; Aguiar et al, 2006, 2008). As detailed in Figure 1, studies performed in different animal models report unequal modification in serotonergic receptor expression along the BG nuclei.…”
Section: Implication Of the Serotonergic System In Parkinson's Diseasementioning
confidence: 88%